(untitled) (The International Journal for Scientific Research, 2024)
This study aims to shed light on the phenomenon of Customer Experience (CX) enhanced by Artificial Intelligence (AI) as a Sustainable Competitive Advantage (SCA) for the relationship marketing industry in general, and Customer Relationship Management (CRM) in particular. It takes into account the great aura of accelerated scientific advancement and accumulated cognitive development on the one hand, and the technical and cyber progress that are expanding at a very rapid pace day after day, on the other hand. These two considerations led to a huge economic revolution that have had a profound impact on all sectors and at various levels. The industrial world moved from the Fourth Industrial Revolution (Industry 4.0) based on Cyber-Physical Systems (CPS), to the Fifth Industrial Revolution (Industry 5.0) which centers on humans and collaborative robots (Cobot). AI algorithms are among the most important outcomes produced by the digital and cloud environment supported by Information and Communications Technology (ICT) and Internet networks (Web 3.0; Web 4.0). These innovative mechanisms revealed their superior and enormous ability as well as their astonishing capability to change the rules of the competitive game and modify the laws of marketing and forces of supply and demand. This theoretical study found that CX personalization is a vital and rich source for the establishing strategic success and sustainable excellence in target markets and managing to overcome and outperform current and potential competitors. It is also considered one of the most important modern marketing approaches that has benefited from: Automation Solutions, Machine Learning (ML), Natural Language Processing (NLP), Large Language Models (LLMs), Generative AI, Big Data Analysis, Internet of Things (IoT) Sensors, Blockchain, Augmented Reality (AR), Virtual Reality (VR), Cloud Computing (CC), and Quantum Computing (QC), ..., etc. The consequences of harnessing and adapting these efficient and effective tools and means to achieve an exceptional performance expected for brands are based on improving and enhancing the CX through Hyper-Customization instead of Mass Customization.